2003
DOI: 10.1046/j.1365-313x.2003.016016.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐DNA recombination and replication in maize cells

Abstract: SummaryT-DNA recombination and replication was analyzed in 'black mexican sweet' (BMS) cells transformed with T-DNAs containing the replication system from wheat dwarf virus (WDV). Upon recombination between the T-DNA ends, a promoterless marker gene (gusA) was activated. Activation of the recombination marker gene was delayed and increased exponentially over time, suggesting that recombination and amplification of the T-DNA occurred in maize cells. Mutant versions of the viral initiator gene (rep), known to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Previous studies have shown that linearized plasmids recircularize in protoplasts (Gorbunova and Levy, 1997;Gallego et al, 2003). However, circularization of ds T-DNAs in plants was considered a relatively rare event until now, because evidence for circularization was indirect and required a viral amplification system (Bakkeren et al, 1989;Zhao et al, 2003). Our ability to detect T-circles directly from infected plants using a plasmid-rescue approach suggests that circularization of ds T-DNAs may not be as rare as previously thought.…”
Section: The Aspects Of In Planta T-dna Circularizationmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies have shown that linearized plasmids recircularize in protoplasts (Gorbunova and Levy, 1997;Gallego et al, 2003). However, circularization of ds T-DNAs in plants was considered a relatively rare event until now, because evidence for circularization was indirect and required a viral amplification system (Bakkeren et al, 1989;Zhao et al, 2003). Our ability to detect T-circles directly from infected plants using a plasmid-rescue approach suggests that circularization of ds T-DNAs may not be as rare as previously thought.…”
Section: The Aspects Of In Planta T-dna Circularizationmentioning
confidence: 68%
“…Sequencing of end-joining junctions in our T-circles revealed that their ends had none or only a few base pairs of overlapping microhomology (Supplemental Fig. S3), thus indicating that our T-circles did not form through homologous recombination, as occurs in A. tumefaciens, but through illegitimate end joining, which is typical of the circularization of T-DNAs in infected plants (Bakkeren et al, 1989;Zhao et al, 2003). Moreover, T-circles containing T-DNAs from different A. tumefaciens strains were generated following coagroinfiltration (Figs.…”
Section: The Formation Of Complex T-circles In Plantsmentioning
confidence: 91%
“…1D). In the case of T-DNA with the simple RMCE cassette, T-DNA border ligation may result in a similar circular substrate, but probably this does not occur frequently (Bundock et al, 1995;Vergunst and Hooykaas, 1998;Zhao et al, 2003). Here, we used a cotransformation approach to introduce Cre recombinase in the same cell as the exchange T-DNAs by means of an Agrobacterium strain harboring a T-DNA vector containing a strong expression unit for the cre gene.…”
Section: Experimental Designmentioning
confidence: 99%
“…Based on several studies, it is known that T-DNA becomes double stranded prior to integration (Offringa et al, 1990;Mozo and Hooykaas, 1992;Narasimhulu et al, 1996;Chilton and Que, 2003;Tzvira et al, 2003). Although circle formation of T-DNA by ligation of the two T-DNA borders has been reported (Bakkeren et al, 1989;Bundock et al, 1995;Zhao et al, 2003), the frequency of occurrence remains unclear. Pansegrau and coworkers (1993) have shown that VirD2 can mediate ligation of the two T-DNA borders in vitro.…”
mentioning
confidence: 99%
See 1 more Smart Citation